Kepemimpinan Etis dan Kultural dalam Pendidikan - Luthfi Anis Muadzin; Sunarto Sunarto (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to describe the importance of ethical and cultural leadership in education, especially in creating a conducive learning environment, which not only focuses on academic achievement, but also on the formation of students' moral character. One of the main challenges in the world of education today is the decline in polite behavior and moral ethics in the school environment, which results in rampant violations of social and religious norms. Ethical and cultural leadership is expected to provide solutions to this problem by instilling strong moral values and maintaining the sustainability of cultural values. This study uses a qualitative approach with a library research method to analyze the concept of ethical and cultural leadership. The results of the study show that ethical educational leaders must uphold the principles of justice, responsibility, and transparency in every action, while cultural leaders must be able to maintain and adapt cultural values to remain relevant to the times. These two types of leadership are expected to create a healthy organizational culture and build integrity in educational institutions, as well as motivate their followers to play an active role in achieving holistic educational goals. Education leaders are expected to be agents of change who are able to balance the preservation of cultural values and the application of innovation in education. Keywords: This study aims to describe the importance of ethical and cultural leadership in education, especially in creating a conducive learning environment, which not only focuses on academic achievement, but also on the formation of students' moral character. One of the main challenges in the world of education today is the decline in polite behavior and moral ethics in the school environment, which results in rampant violations of social and religious norms. Ethical and cultural leadership is expected to provide solutions to this problem by instilling strong moral values and maintaining the sustainability of cultural values. This study uses a qualitative approach with a library research method to analyze the concept of ethical and cultural leadership. The results of the study show that ethical educational leaders must uphold the principles of justice, responsibility, and transparency in every action, while cultural leaders must be able to maintain and adapt cultural values to remain relevant to the times. These two types of leadership are expected to create a healthy organizational culture and build integrity in educational institutions, as well as motivate their followers to play an active role in achieving holistic educational goals. Education leaders are expected to be agents of change who are able to balance the preservation of cultural values and the application of innovation in education.